2017
DOI: 10.1177/0163443717746229
|View full text |Cite
|
Sign up to set email alerts
|

Self-represented witnessing: the use of social media by asylum seekers in Australia’s offshore immigration detention centres

Abstract: The act of witnessing connects audiences with distant suffering. But what happens when bearing witness becomes severely restricted? External parties, including the mainstream news media, are constrained from accessing Australia’s offshore immigration detention centres. The effect is that people seeking asylum are hidden from the public and excluded from national debates. Some detainees have adopted social media as a platform to communicate their stories of flight, and their experiences of immigration detention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 28 publications
0
28
0
2
Order By: Relevance
“…In the interactions with family members and relatives, migrants tried to manage their self-presentation stressing the positive aspects of their life away from home rather than their everyday life difficulties. In addition, in line with Rae et al [40], Witteborn [25] found that mobile technologies allowed migrants to present to society at large by overcoming their perceived invisibility and making themselves visible as a political force that comes up with ideas, and mobilizes and claims their own rights.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In the interactions with family members and relatives, migrants tried to manage their self-presentation stressing the positive aspects of their life away from home rather than their everyday life difficulties. In addition, in line with Rae et al [40], Witteborn [25] found that mobile technologies allowed migrants to present to society at large by overcoming their perceived invisibility and making themselves visible as a political force that comes up with ideas, and mobilizes and claims their own rights.…”
Section: Resultsmentioning
confidence: 73%
“…Lastly, two articles consider the potential of digital technology, especially social media networks, as ‘digital witnesses’ of the sufferings documented by refugees and shared by them on platforms such as Facebook. In their study, Rae, Holman and Nethery [40] analyzed how social media, accessed primarily using MPs, became a vital tool for asylum seekers within Australian offshore detention facilities to connect with journalists, advocates, activists, legal representatives and family and friends. Through an analysis of two Facebook pages accessible to the general public–related to the case of a Kurdish journalist and Iranian national, Behrouz Boochani, and to the case ‘free the children NAURU’ dedicated to asylum seekers’ children detained in Nauru–Rae and colleagues showed that detainees circumvented the usual mediation of their stories and engaged in a self-represented witnessing.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in a gradual transformation of social and educational structures for Somali women in the camps and those who stayed in Somalia, challenging the current status quo that constrains them to pursue higher education (Dahya & Dryden‐Peterson, 2017). Finally, studies highlight that social networks accessed primarily through mobile phones gave asylum seekers and detainees visibility in the public space that allowed for positioning themselves legally and politically to defend their own rights (Coddington & Mountz, 2014; Leung, Lamb, & Emrys, 2009; Rae, Holman, & Nethery, 2018; Witteborn, 2018). Stavinoha (2019) conceptualizes these mediated practices of claims‐making and political agency among refugees as “communicative acts of citizenship,” with the potential to both reinforce and challenge oppressive and exclusionary policies in different contexts of protracted displacement.…”
Section: Mobile‐mediated Experiences Of Protracted Displacementmentioning
confidence: 99%
“…Even though media oten rehumanizes refugees (Wallace 2018, 22) the sentimental portrayal of refugee stories as tragedies can be harmful in diferent ways. Instead of mobilizing public and political agency, media coverage of migration ends up creating spectacles of human sufering, turning reporting into acts of voyeurism and raising "vague awareness" of largely apathetic spectators (Rae et al 2017;Chouliaraki and Stolić2017). Based on the analysis of our corpus, we suggested that the circulation of stances through sharing visual small stories creates alignment frames that guide the reception of this story in relation to other stories.…”
Section: Resultsmentioning
confidence: 97%